Research Progress of Laser Induced Metal Surface Coloring Technology - Zheng, Zhihui; Wei, Xinlei; Lin, Yingyi; Dong, Tianyuan; Zheng, Siyuan; Shao, Wenjie; Kang, Jianli; Mei, Guoqing (International Journal of Materials Science and Technology Studies, 2024)
Laser-induced metal surface coloring technology combines the advanced manufacturing technology of modern laser technology and material science. It no longer relies on dyes or chemicals to achieve material surface coloring, but makes use of the characteristics of the interaction between laser and metal materials. Through the precise control of laser parameters (such as wavelength, pulse width, energy density, etc.), complex micro-structures can be formed on the metal surface, thus changing its optical properties. To achieve the coloring effect, compared with the traditional coloring method, it has significant advantages such as no pollution, high precision, strong flexibility and so on. This paper deeply discusses the core principle of laser-induced metal surface coloring, systematically analyzes the evaluation criteria of coloring quality, and focuses on the key factors affecting the induced coloring process. Despite its strong application potential, laser-induced metal surface coloring technology still lacks sufficient key data support for constructing an accurate coupling model between laser parameters and coloring effect. This hinders the achievement of high controllability, reproducibility, durability, and stability of surface shading colors. Therefore, it is necessary to further focus on these core issues and accumulate more experimental data through fine experimental design and advanced characterization technology, so as to promote the continuous optimization and wide application of laser-induced metal surface coloring.